Evaluation of multi-angle imaging with planar organ-targeted positron emission tomography detectors - Shahi, Anirudh (My University, 2024)
Positron Emission Tomography (PET) with 2-[fluorine-18]-fluoro-2-deoxy-D-glucose (18F-FDG) is a functional imaging modality which is capable of detecting cancer tumors based on their increased metabolic activity – a fingerprint of cancer. This capability makes PET a key tool in oncology for cancer detection. PET imaging increasingly requires the visualization of specific organs with organ-targeted PET systems in response to the clinical need to enhance the diagnostic capabilities of PET imaging. Organ-targeted PET detectors offer improved sensitivity and spatial resolution compared to conventional whole-body (WB) PET systems. However, ring-based organ-targeted PET detectors have a fixed diameter optimized for imaging a single organ, which limits their clinical utility. In contrast, planar PET detectors, consisting of two flat panels with adjustable separation, offer greater versatility for imaging multiple organs. However, planar PET detectors have limited angular coverage, which leads to image distortion (smearing) along the axis perpendicular to the detector plane. This smearing degrades the quality of 3D reconstructed images and reduces the accuracy of activity estimation in small lesions. The objective of this Thesis is to improve the effective angular coverage of planar PET detectors by introducing detector rotations in a method called multi-angle image acquisition and reconstruction. Experiments were conducted using the Radialis PET camera, a planar organ-targeted PET detector designed for 2D breast cancer imaging. While Radialis organ-targeted PET technology significantly improves 2D visualization of breast lesions compared to traditional WB-PET systems, its 3D imaging capabilities are limited due to insufficient angular coverage. The experiments with simulated, standard and custom-made phantoms filled with 18F-FDG solutions demonstrated that multi-angle acquisition and reconstruction improves image quality, eliminates image artifacts and provides more accurate quantitative estimates inside the phantoms, attributable to the increased effective angular coverage. Overall, the findings of this Thesis suggest that multi-angle imaging with planar PET detectors can achieve full 3D reconstruction, broadening the potential for multi-organ imaging with planar organ-targeted PET systems.